Pintakasvillisuuden torjunnan tehokkuus vaikuttaa männyn kasvuun pellonmetsityksessä. - Hytönen, Jyrki; Jylhä, Paula (Metsäntutkimuslaitos, 2010)
Seloste artikkelista: Hytönen, J. & Jylhä, P. 2010. Long-term response of weed control intensity on Scots pine survival, growth and nutrition on former arable land. European Journal of Forest Research. DOI10.1007/s10342-010-0371-6.